Effect of hesperetin on inflammatory and oxidative status in trinitrobenzene sulfonic acid-induced experimental colitis model - Polat, Fatin Rustu; Karaboga, Ihsan; Polat, Muhammed Semih; Erboga, Zeynep; Yilmaz, Ahsen; Güzel, Savas (Cellular and Molecular Biology, 2018)
In our study, the effect of hesperetin on inflammatory and oxidative status in trinitrobenzene sulfonic acid (TNBS)-induced experimental colitis model was investigated through different methods. Eighteen Wistar albino male rats were divided in to three groups: Group I (Control, n = 8; 1 ml physiological saline), Group II (Colitis, n = 8; 1 ml TNBS), Group III (Hesperetin, n = 8; 1 ml TNBS and 100 mg/kg hesperetin). Macroscopic and microscopic scores were calculated to determine the damage to the colon at the end of the experiment. Serum tumor necrosis factor-Î± (TNF-Î±) and tissue interleukin-6 (IL-6) levels were determined using the ELISA method. Myeloperoxidase (MPO), superoxide dismutase (SOD), catalase (CAT) and malondialdehyde (MDA) levels were investigated spectrophotometrically. The TUNEL method was used for the detection of apoptotic cells in the colon tissue. Inducible nitric oxide synthase (iNOS) and nuclear factor-kappa-B (NF-Ä¸Î²) expression in the colon were determined immunohistochemically. Hesperetin administration has shown to significantly reduce levels of MPO, MDA, and proinflammatory agents (TNF-Î±, IL-6, and NF-Ä¸Î²). It has also been proven to inhibit mucosal apoptosis. This study indicates that hesperetin is protective against TNBS-induced colitis model via antiinflammatory, antioxidant and antiapoptotic effects.